2023
DOI: 10.3390/socsci12020074
|View full text |Cite
|
Sign up to set email alerts
|

“All Is Fair in… Meme!” How Heterosexual Users Perceive and React to Memes, News, and Posts Discriminating against Sexual Minorities

Abstract: Digital discrimination against sexual minorities is becoming prevalent. It increasingly spreads through discriminatory content that mixes text and images (e.g., memes), thus, making online discrimination more difficult to detect. The present survey study focused on digital content that is discriminatory towards sexual minorities, aiming to analyze whether a sample of heterosexual social network users (65.2% female; Mage = 27.13) perceived different forms of discriminatory content (i.e., memes, news, and posts)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Spontaneous platforms such as social networks would be therefore more appropriate for maintaining intergroup contact than initiating it (Hasler & Amichai-Hamburger, 2013). Some studies confirmed that interacting on social network with an outgroup member reduced prejudice , increased sensitivity to discriminatory content circulating on the Web (Mancini & Imperato, 2020), and improved the willingness to counter it (Imperato et al, 2023) and to act antiracist behaviours (Imperato, Keum, & Mancini, 2021).…”
Section: Online Intercultural Dynamics and Intercultural Sensitivitymentioning
confidence: 99%
“…Spontaneous platforms such as social networks would be therefore more appropriate for maintaining intergroup contact than initiating it (Hasler & Amichai-Hamburger, 2013). Some studies confirmed that interacting on social network with an outgroup member reduced prejudice , increased sensitivity to discriminatory content circulating on the Web (Mancini & Imperato, 2020), and improved the willingness to counter it (Imperato et al, 2023) and to act antiracist behaviours (Imperato, Keum, & Mancini, 2021).…”
Section: Online Intercultural Dynamics and Intercultural Sensitivitymentioning
confidence: 99%
“…The proliferation of the internet has revolutionized communication and interaction, making it more accessible and convenient. Digital spaces have facilitated the establishment and maintenance of interpersonal connections, allowing individuals to find others who share similar interests (Imperato et al, 2023). Memes, which are images combined with text to convey ideas, have gained immense popularity in the online world.…”
Section: Introductionmentioning
confidence: 99%